Standardization of International Marketing Strategy: Some Research Hypotheses - Jain, Subhash C. (Journal of Marketing, 1989)
Two aspects of international marketing strategy standardization are process and program standardization. A framework for determining marketing program standardization is introduced. Factors affecting program standardization are examined critically. In an attempt to establish a research agenda on the standardization issue, the author develops research propositions for each factor.